September strategising - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The European Forum for Rural Development Cooperation will be held in Montpellier, France, 4-6 September 2002. Organiser: the European Commission with France s foreign affairs ministry, donor and CTA support, and much Southern partner input....